The Rab5 effector Rabankyrin-5 mediates endosomal fusion and trafficking of human papillomavirus during early entry - Madison Love; Richard C. Dang; Jian Xie; Pengwei Zhang (Proceedings of the National Academy of Sciences, 2026)
The fusion of newly formed early endosomal vesicles after endocytosis is a crucial step in viral infection. It facilitates the transition of many viruses from viral internalization to downstream intracellular trafficking within the endosomal network, ultimately enabling their delivery to intracellular replication sites. Despite its significance, the molecular mechanisms regulating the fusion of these vesicles remain poorly understood. In this study, we show that Rabankyrin-5, a Rab5 effector, is essential for the fusion of human papillomavirus (HPV)-carrying early endosomes during viral entry. Additionally, Rabankyrin-5 acts as a dynein adaptor, directly binding both the HPV minor capsid protein L2 and the dynein motor complex to link virus-carrying early endosomes to the dynein transport machinery, thereby promoting virus movement along microtubules. These dual functions enable the coordinated integration of endosomal fusion with microtubule-based transport during the early stages of viral entry.